Analisis Framing Konten Black Campaign @ecinos: Terkait Respon Publik - Bintang Nuraeni; Detya Wiryany (Penerbit Jurnal Indonesia, 2026)
This study analyzes the framing of @ecinos content that constructs a black campaign narrative against Uniqlo and Hulm and identifies public responses to the narrative. A descriptive qualitative approach was employed using the Pan and Kosicki framing model, encompassing syntactic, script, thematic, and rhetorical dimensions. The data were derived from social media content and user comments on Instagram, TikTok, and X, complemented by in-depth interviews with marketing communication practitioners. The findings indicate that Ecinos frames its competitors as less advantageous by emphasizing higher prices and perceived disproportionate quality, while simultaneously positioning its own brand as a more rational and reasonable choice. This framing pattern generates a predominance of negative public responses, including expressions of disappointment and calls for boycotts. At the same time, the reactions reflect an increasing level of public awareness and sensitivity toward black campaign practices. Practitioners interviewed in this study argue that such strategies pose significant risks, particularly in undermining consumer trust and eroding brand equity in the long term. Overall, the study highlights the strategic implications of framing in social media-based competitive communication and its potential consequences for brand sustainability.